Community Education for Rape Insulated Women Entrepreneurship in Akoko Land - Ayimoro, Oluwatoyin Dorcas (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The study had the desire of advancing whether Community education could assist in building a rape insulated women entrepreneurship in Akoko land. It does this by examining the demographic representation of the rape victims/ survivors, the pattern in which the survivors were raped, the effect on them, succor received, the punishment meted on the perpetrators and how community education could assist in curbing the menace. Linear snowball sampling technique was used to select twelve (12) women entrepreneurs that hawk/peddle finished products of their enterprises and who were victims/survivors of rape from the four (4) purposively selected skills (bakery, fishery, poultry and water processing). The study adopted frequency count, percentages and qualitative summaries in analyzing the data received. It was found that, rape is prevalent among peddlers of goods from enterprises, the pattern of exposure to rape among victims differs, excessive trepidation among the victims worked against building confidence to speak out, patriarchy, traditional stereotypes, gender inequalities, inefficiency and ambiguity in laws obstructed the prosecution of perpetrators of rape and growth of entrepreneurship in the study area. It was recommended among others, that a dire need of utilising the potentials in community education through concerted effort of all will assist in dousing the intense heat generated by rape in our society. Keywords: Community education, women entrepreneurs, rape victims and insulation.